2014
DOI: 10.1515/chem-2015-0058
|View full text |Cite
|
Sign up to set email alerts
|

Low pressure RF plasma modification of the surface of three different nano-carbon materials

Abstract: Well-ordered nano-carbon materials, like multiwall carbon nanotubes, graphene oxide, graphene due to their unique physical and chemical properties, are candidates for promising applications.In this work thin multilayered graphene, single layer graphene oxide layers and highly oriented pyrolytic graphite (HOPG) surface were treated by RF activated N 2 gas plasma at nominally room temperature. Negative bias in the 0-200 V range and treatment time of 10 min was applied. Surface chemical alterations were followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Experiments, performed using similar conditions on other nanocarbon materials (e.g. graphene, nanotubes, or graphite), showed that similar chemical states were developed, although with different quantitative distributions.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Experiments, performed using similar conditions on other nanocarbon materials (e.g. graphene, nanotubes, or graphite), showed that similar chemical states were developed, although with different quantitative distributions.…”
Section: Resultsmentioning
confidence: 93%
“…Reliability of the results published so far is often suffering from insufficient characterization of the modified surface. We have been conducting detailed studies on this topic …”
Section: Introductionmentioning
confidence: 99%